Au-delà de l'État. La vie sociale des pesticides dans le secteur maraîcher au Bénin - Roch Appolinaire Houngnihin; Pascal Mègnissè Gbégan; Dimi Theodore Doudou (VertigO)
In southern countries, urban agriculture is often criticized because of its polluting practices due, to a large part, to the non-standard use of pesticides on market garden sites. The relationships between the actors involved in the design and implementation of public policies constitute one of the causality registers of these practices. This article aims to list and describe the actors structuring the uses of pesticides in urban agriculture in Benin, as well as their interactions. The methodological device is an ethnographic type based on the review of texts relating to pesticides, in-depth interviews, and direct observations on market garden sites in Benin's three main urban areas: Cotonou, Porto-Novo and Parakou. In total, 55 actors from different profiles were surveyed. Several categories of people are involved in market gardening sites. Faced with logics involved (both divergent and contradictory), the "social life" of the pesticide escapes the control of public institutions. The knowledge of producers and sellers prevails over official recommendations. Likewise, the institutional vacuum created by public sector agents is filled by some specific actors, the "distributor-framers". In addition, intergenerational conflicts between producers, aroused by political intrigue, are recurrent in access to available material and financial resources. Such situations weaken the sector of the market garden and interfere negatively in the implementation of public policies relating to pesticides.